FAZLUR RAHMAN DAN METODE IJTIHADNYA: Telaah Sekitar Pembaruan Hukum Islam - Husein Alyafie (State Institute of Islamic Studies (IAIN) Palu, 2009)
In his monumental work, Islamic Methodology in History, Fazlur Rahman proposed two causes of failure of using ijtihâd as a method in interpreting Islamic law among classical Islamic law scholars. Firstly, there is an unharmonious relationship between “sunnah-ijma’-ijtihâd; secondly, there is a burden of majority doctrine theology towards the law. Both causalities are related each other. Fazlur Rahman tried to show the unharmonious between “sunnah-ijma’-ijtihâd” as stated in usûl fiqh. In those unharmonious relationship, ijtihâd is defeated by ijma’. In fact, ijtihâd is regarded as a means to direct and to form ijma’. Due to the ineffective position of ijtihâd, it is not possible to form new ijma’.Kata Kunci: Fazlur Rahman, metode ijtihad, pembaruan hukum Islam, sunah, ijmak